Analisis Kendala Pembelajaran E Learning pada Era Disrupsi di SMK Terpadu Al-Islahiyah Singosari Malang - Shobich Ulil Albab (Mudir : Jurnal Manajemen Pendidikan, 2020)
In this era of disruption, education as a reference in implementing national education goals has a very important role in the development of education in school institutions, in this case all components of education are required to master the field of technology. Because in that era there was a change of learning, from classical to computerized era. This is not surprising because in the twenty-first century, the role of technology is very important, especially in the case of computerization. One form of this change is the onset of online-based learning or commonly referred to as e-learning learning in educational institutions. Because in learning e-learning besides there are many benefits that are obtained or generated. Learning with this method requires internet access and various other components to support the learning process. But there are also various obstacles experienced by this online learning (e learning). One of them is the social, family and community environment and economic differences of each of the different students which become obstacles in this online-based learning. Obstacles or obstacles in applying methods do always exist in an educational process.